Socialization Of The Business World - The Industrial World As An Implementation Of The Independent Learning Policy - Independent Campus At The Faculty Of Social And Political Sciences, Riau University - Bambang Suwarno; Zuhri Ramadhan; Bhakti Alamsyah; Jhon Simon (International Journal Of Community Service, 2022)
During the Covid-19 pandemic, the pattern of education has changed. From a face-to-face teaching system to a teaching and learning process carried out remotely by utilizing the internet and information and communication technology. The Merdeka Belajar – Kampus Merdeka policy applied by the government to universities has created interesting dynamics for universities. One of these policies is internship/work practice in the industrial world. It is hoped that universities and their alumni can be independent, and graduates are able to work with the knowledge and skills they have so that they can provide benefits for the community to maintain a work environment in the industry. The purpose of this service is to socialize business world - industrial world to universities within the Faculty of Social and Political Sciences, University of Riau. Community service is carried out in the form of seminars and collaboration in the business world and industry. The method used in the implementation of this service is direct collaboration with distributors of e-learning companies and international work internships at PT. Anugrah Rezeki Sejahtera with its products, namely Altissia (elearning 22 language program), SmartInternz (IT project e-learning program) and Sea Education (cruise ship internship program).